Relationship Between Nutritional Status and Fine Motor Skill Development of Class B PAUD Students in Kediri District, West Lombok - Nina Anggraini; Kusmiyati Kusmiyati; Dewa Ayu Citra Rasmi (Jurnal Biologi Tropis, 2026)
This original research paper employs a quantitative cross-sectional analytic design to investigate early childhood development in a specific Indonesian setting. This study aimed to analyze the relationship between nutritional status and fine motor skill development in class B preschool children (aged 5–6 years) in Kediri District, West Lombok, Indonesia. A quantitative cross-sectional analytic design was used. The sample consisted of 67 children from five PAUD selected by proportional random sampling. Nutritional status was assessed using BMI-for-age (IMT/U) based on WHO standards, while fine motor skill development was measured through structured observation using seven indicators. Data were analyzed using Chi-Square and Fisher's Exact Test. Results showed that most children had normal nutritional status (67.1%), 29.9% were undernourished, and 1.5% each were overweight and obese. Fine motor skill development was in the "Very Well Developed" category for 76.1% of children and "As Expected" for 23.9%. Statistical evaluation showed no meaningful connection between nutritional status and the development of fine motor skills (p = 0.756 > 0.05). While descriptively a larger percentage of kids with "Very Well Developed" fine motor skills was noted in the normally nourished group (80.0%) than in the undernourished group (75.0%), the disparity was not statistically important. This study concludes that nutritional status does not have a significant link to the growth of fine motor skills in early childhood education (PAUD) Grade B children in the Kediri District of West Lombok.